Review and trend analysis of slow tourism as an emerging trend in the Indonesian tourism industry: A study of why there is lack of extensive discussion on this topic - Supina, Supina; Ichsan Banse, Justin Mochammad (Journal of Indonesian Tourism, Hospitality and Recreation, 2023)
ABSTRACTThe COVID-19 pandemic has led to a surge in the appeal of "slow tourism,"  which denotes relaxed and unhurried vacations for tourists. Slow tourism encourages tourists to fully appreciate each moment, immerse themselves completely in the rich tapestry of local culture, and establish profound bonds with the varied Indonesian communities and landscapes that constitute this captivating nation. The principles of this "slow tourism" should be well rooted in Indonesia, particularly in rural regions, where longstanding customs have traditionally welcomed visitors to engage in culturally immersive encounters. The emergence of the "slow tourism" phenomenon occurred during the latter part of the 20th century and the early part of the 21st century. This study originates from an investigative journey to evaluate the present patterns and execution of "slow tourism" in Indonesia. This study employs a comprehensive examination of secondary data, encompassing scholarly research, and publications from the tourism sector by using VOSviewer, to furnish detailed insights into the evolution of this nascent paradigm. The objective is to promote conscientious travel behaviours and safeguard the nation's ecological and cultural legacy for future enerations. The study's findings offer comprehensive guidance, practical recommendations, and a theoretical framework for policymakers, researchers, and industry stakeholders.ABSTRAKPandemi COVID-19 telah meningkatkan daya tarik “pariwisata lambat”, yang berarti liburan santai dan tidak terburu-buru bagi wisatawan. Pariwisata lambat mendorong wisatawan untuk sepenuhnya mengapresiasi setiap momen, membenamkan diri sepenuhnya dalam kekayaan budaya lokal, dan menjalin ikatan mendalam dengan beragam komunitas dan lanskap Indonesia yang membentuk negara menawan ini. Prinsip-prinsip “pariwisata lambat” ini harus berakar dengan baik di Indonesia, khususnya di daerah pedesaan, di mana adat istiadat yang sudah lama ada secara tradisional menyambut pengunjung untuk terlibat dalam perjumpaan budaya yang mendalam dan mendalam.Munculnya fenomena ini terjadi pada akhir abad ke-20 dan awal abad ke-21. Penelitian ini bermula dari perjalanan investigasi untuk mengevaluasi pola dan pelaksanaan “slow pariwisata” saat ini di Indonesia. Studi ini menggunakan pemeriksaan komprehensif terhadap data sekunder, yang mencakup penelitian ilmiah dengan menggunakan VOSviewer, dan publikasi dari sektor pariwisata, untuk memberikan wawasan rinci mengenai evolusi paradigma yang baru lahir ini. Tujuannya adalah untuk mendorong perilaku perjalanan yang berhati-hati dan menjaga warisan ekologi dan budaya bangsa untuk generasi masa depan. Temuan studi ini menawarkan panduan komprehensif, rekomendasi praktis, dan kerangka teoritis bagi pembuat kebijakan, peneliti, dan pemangku kepentingan industri.